Case report: Cerebrotendinous Xanthomatosis masquerading as adult ADHD in psychiatric practice - Jongtae Kim; Yun Jeong Hong; Si Baek Lee; Seong Hoon Kim; Myung Ah Lee; Eunbuel Ko; Jeong Wook Park (Frontiers in Psychiatry)
IntroductionThis case report details the presentation of a patient who initially sought consultation at a psychiatric outpatient clinic with symptoms suggestive of Attention-Deficit/Hyperactivity Disorder (ADHD); however, further evaluation revealed a diagnosis of Cerebrotendinous Xanthomatosis (CTX). CTX, a genetic disorder impacting lipid metabolism, is often overlooked in differential diagnoses due to its rarity. This case underscores the importance of considering alternative diagnoses in adults exhibiting ADHD-like symptoms without a childhood history of the disorder, adding to the literature on diagnostic complexities in psychiatric practice.Case presentationA 33-year-old man visited a psychiatric outpatient clinic with symptoms such as increasing distractibility and inattention, requesting an evaluation for adult ADHD. However, the absence of an ADHD history in childhood, coupled with progressive neurological symptoms and tendon xanthomas, led to further investigation. Comprehensive neurological assessments, including neuroimaging and genetic testing, ultimately diagnosed him with CTX. Treatment with chenodeoxycholic acid (CDCA) resulted in stabilization of cognitive function, although improvement in gait disturbances and tremors remained minimal.ConclusionThis case demonstrates that CTX can masquerade as adult ADHD, emphasizing the necessity for thorough assessments in atypical ADHD presentations. Psychiatrists should consider rare metabolic disorders like CTX in similar cases, which may enable timely intervention and improve patient outcomes.